1964
DOI: 10.1121/1.1939223
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Properties of Sediments

Abstract: This is a summary of work done at DRL on measurement of acoustic properties of water-saturated sediments. The sediments used were laboratory-prepared to allow control of physical parameters (such as grain size, volume concentration, compressibility, etc.) and to approximate natural sediments. Acoustic velocity and attenuation in the sediments were measured over the frequency range 4–600 kc/sec. Acoustic measurements were made at high frequencies by means of two probes inserted in the sediments and at low frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…Nolle et al ͑1963͒ found the f 1/2 dependence of attenuation coefficient in water-saturated sands at frequencies of 0.2, 0.5, and 1.0 MHz. In contrast, most data exhibit a linear scaling of attenuation coefficient with frequency over a wide range of frequencies ͑Wingham, 1985; Hamilton, 1987͒, which is consistent with the prediction of the GS model based on grain-to-grain shearing mechanisms ͑Buckingham, 1997͒. In fact, the GS model yields an attenuation coefficient that is almost but not quite linear in frequency.…”
Section: Introductionsupporting
confidence: 78%
“…Nolle et al ͑1963͒ found the f 1/2 dependence of attenuation coefficient in water-saturated sands at frequencies of 0.2, 0.5, and 1.0 MHz. In contrast, most data exhibit a linear scaling of attenuation coefficient with frequency over a wide range of frequencies ͑Wingham, 1985; Hamilton, 1987͒, which is consistent with the prediction of the GS model based on grain-to-grain shearing mechanisms ͑Buckingham, 1997͒. In fact, the GS model yields an attenuation coefficient that is almost but not quite linear in frequency.…”
Section: Introductionsupporting
confidence: 78%
“…The corresponding acoustical signals were recorded on a sampling oscilloscope and transmitted to a PC for processing. To obtain the phase speed, the following relation was used [15]: (3) where and are the Fourier transform of the signal received after propagating through sand and water, respectively, is the distance between the transmitter and the receiver, and is the time of arrival of the signal, which has been defined above. In this case, only one distance was required for phase-speed measurements.…”
Section: Sound-speed Measurementsmentioning
confidence: 99%
“…Such a behavior is observed in the case of solid lipid nanoparticle (SLN) too. The variation of ultrasound velocity with concentration of suspended particle has been reported by several authors [45][46][47][48][49][50]. They showed that the ultrasound velocity is significantly influenced by the solid fraction in suspension.…”
Section: Acoustic Parametersmentioning
confidence: 87%